OPTIMALISASI POSTER SEBAGAI UPAYA PENURUNAN HIPERTENSI DI RT 24 REJOWINANGUNG, KOTAGEDE, YOGYAKARTA - Suci Musvita Ayu; Erni Cipta Komala (COVIT (Community Service of Health), 2022)
Hypertension is a condition in which a person experiences an abnormal and continuous increase in blood pressure on several examinations. Hypertension is characterized by blood pressure readings that exceed a value of more than 140 mmHg (systolic) and 90 mmHg (diastolic). Hypertension is a cardiovascular disease that can cause other diseases such as stroke, diabetes mellitus and coronary heart disease. The purpose of this activity is to reduce the incidence of hypertension and increase public knowledge. This activity was held in RT 24, Rejowinangun, Kotagede, Yogyakarta. This activity begins with collecting data, determining the priority of the problem, after that it is continued with the distribution of posters to the surrounding community. In this activity, the community was very enthusiastic in carrying out this activity. Keywords: Hypertension, Public